A brief review on the latest applications of fibrous materials in advanced and emerging areas - Fangueiro, Raúl (2013)
Fibrous materials are finding widespread applications in diversified areas, starting from clothing sector to medical fields, various structural and infrastructural applications of civil engineering, aerospace industries and even for energy generation and storage applications. In this paper, some of the most recent research studies on the application of fibrous materials in various advanced sectors have been reviewed and presented.